How is Confidence Related to Unemployment in Europe? A fuzzy logic answer - Caleiro, António (2013)
Notwithstanding the numerous applications of fuzzy logic in several fields of economics, it is surprising that, to the best of our knowledge, so very few applications have been made in modelling approximations of subjective economic variables, such as confidence, satisfaction or even expectations, by objective ones, such as unemployment, output or inflation. This gap in the literature is accompanied by a lack on the availability of data concerning those subjective variables. Given that one of the main concerns of fuzzy logic is to capture approximate rather than exact forms of reasoning, and this also characterises many economic situations, such as in fact forming intrinsically subjective measures of confidence, this logic can and should indeed be used to understand how some of those subjective measures can be approximated by objective ones. This task is accomplished in the paper by the use of data on consumer confidence and on the unemployment rate for the pre-enlargement fifteen European Union member states. The results indicate the clear importance of unemployment on confidence, which is a result that should be taken into account when analysing policy-making that, from a naïve and/or easy viewpoint, considers confidence as a relevant variable but ignores unemployment.